The other as my equal - Rasoulipour, Rasoul (Poligrafi, 2020)
The tremendous human capacity to “love” one another is, in my opinion, the strongest evidence both for the existence of God and for the relationship that God intends for human beings to have with God and with each other. At the same time, the human capacity for envy, hate, aggression, and violating the dignity of “other” humans is similarly great evidence that something is horribly wrong - hu-man beings fail to maintain the intended relationship with God and each other. God’s intention does not change, but we forgetful human beings lose sight of it from time to time. This problem is at the root of human alienation from God and others that leaves us isolated, oblivious, suspicious and fearful. This paper intends to provide a framework that allows us to see the source of the problem, to explore some of the causes for human alienation from each other and creation, and to find ways to heal the gap between ourselves and the rest of God’s creation. I believe that all struggles, oppressions and sufferings result from this alienation, and a substantial mission of all religions, at least the Abrahamic religions, is to heal this divide by seeing the other as one’s equal.
Keywords: alienation; človeško dostojanstvo; drugi; enakost; equality; human dignity; odtujitev; stronger; the other; tujec